NIR photoluminescence and radioluminescence characteristics of Nd3+ doped BaTa2O6 phosphor - SAMUR, RAMAZAN (WILEY, 2018)
Barium tantalate phosphors activated with different concentrations of Nd3+ ion were synthesized via conventional solid state reaction method. The synthesized ceramic powders were characterized by X-ray diffraction (XRD), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), laser diode (LD) excited near infrared (NIR) photoluminescence and X-ray induced radioluminescence (RL) analyses. In XRD results, Nd3+ doped BaTa2O6 structure with tetragonal tungsten bronze (TTB) symmetry was observed to continue up to 10 mol%. In the examination of ceramic powders by SEM, grain size decreased with the increasing doping concentration. By using laser diode excited NIR photoluminescence of BaTa2O6:Nd3+ phosphor exhibited characteristic emissions at 877, 1080, and 1376 nm wavelengths due to F-4(3/2) I-4(11/2), F-4(3/2) I-4(11/2), and F-4(3/2) I-4(11/2) band transitions respectively. Scintillation properties of Nd3+ doped samples from UV to near-IR spectral region were carried out by the radioluminescence analysis. NIR and scintillation emissions initially increased by the doping concentration, and then decreased due to concentration quenching effect.
Keywords: photoluminescence; radioluminescence; scanning electron microscopy; tantalum; tantalum compounds; SCINTILLATION PROPERTIES; CRYSTAL-CHEMISTRY; LUMINESCENCE